Myxoid Plexiform Fibrohistiocytic Tumor Masquerading as Ganglion Cyst: A Case Report and Literature Review - Chih-Yi Liu; Jui Lan; Hsuan-Ying Huang (Case Reports in Pathology, 2017)
Background. Plexiform fibrohistiocytic tumor is a distinctive mesenchymal neoplasm of low-grade malignancy, with the capacity for biphasic differentiation toward a fibroblastic or histiocyte-like morphology. Clinically, these lesions affect different areas of the body and appear as painless, slowly growing, dermal or subcutaneous masses. To date, only three cases of myxoid variant have been reported in the English literature. Case Presentation. A 45-year-old female patient presented with a subcutaneous nodule in the right popliteal fossa. The initial impression was a benign ganglion cyst. The soft tissue tumor has been treated by local excision. The histopathological and the immunohistochemical findings supported the diagnosis of myxoid plexiform fibrohistiocytic tumor. The postoperative course was uneventful, and the patient received regular follow-up examination. She is alive without any recurrence. Conclusions. This case demonstrates how to distinguish this distinctive plexiform fibrohistiocytic tumor from other problematic soft tissue tumors. It is also remarkable for its rarely reported extensive myxoid change. Currently, there is no clear-cut correlation between the clinicopathologic findings and the behavior of this unusual variant.